2020
DOI: 10.20960/nh.03214
|View full text |Cite
|
Sign up to set email alerts
|

Post-menopausal osteoporosis: do body composition, nutritional habits, and physical activity affect bone mineral density?

Abstract: Post-menopausal osteoporosis: do body composition, nutritional habits, and physical activity affect bone mineral density? Osteoporosis posmenopáusica: ¿afectan a la densidad mineral ósea la composición corporal, los hábitos nutricionales y la actividad física?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A cross-sectional research of 100 premenopausal women in Spain found a negative connection between coffee intake and BMD, as evaluated by quantitative ultrasonography. [30] Caffeine and caffeine metabolites may have a role in the development of osteoporosis, according to this body of data. Furthermore, caffeine and BMD were examined at multiple places in a Mendelian randomized trial from Sweden, but no causal relationship was found.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional research of 100 premenopausal women in Spain found a negative connection between coffee intake and BMD, as evaluated by quantitative ultrasonography. [30] Caffeine and caffeine metabolites may have a role in the development of osteoporosis, according to this body of data. Furthermore, caffeine and BMD were examined at multiple places in a Mendelian randomized trial from Sweden, but no causal relationship was found.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 , 24 ] Nonetheless, other studies refute this conclusion, with one cross-sectional study of 100 premenopausal women in Spain reporting that coffee consumption negatively affected BMD as measured by quantitative ultrasonography. [ 25 ] These findings suggest that caffeine and caffeine metabolites may play a role in the development of osteoporosis. In our study, we found a U-shaped relationship between urinary theophylline, urinary paraxanthine, and BMD, with inflection points at levels of 0.006 mmol/L for theophylline and 0.052 mmol/L for paraxanthine.…”
Section: Discussionmentioning
confidence: 99%
“…Definition: Osteoporosis is defined by the World Health Organization as a condition affecting the bones on a systemic level, marked by reduced bone density, deterioration of bone structure, and a higher likelihood of suffering from fractures due to fragility, with hip fractures being the most severe outcome [1]. In osteoporosis can be divided into two main categories: primary and secondary osteoporosis.…”
Section: Osteoporosismentioning
confidence: 99%